2021
DOI: 10.1097/scs.0000000000007590
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Neurotization in the Setting of Facial Paralysis: A Comprehensive Review of Surgical Techniques

Abstract: Neurotrophic keratopathy is characterized by decreased corneal sensitivity, decreased reflex tearing, and poor corneal healing resulting in corneal injury. Without proper sensory innervation, the cornea undergoes continuous epithelial injury, ulceration, infection and eventually results in vision loss. In situations where patients have concomitant facial paralysis, such as after resection of a large vestibular schwannoma, the ocular health is further impaired by paralytic lagophthalmos with decreased eye closu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…It is vital to thoroughly understand the mechanisms of the blink reflex when discussing trigeminal nerve damage combined with facial nerve damage. The corneal blink reflex is a loop between the facial nerve and the ophthalmic branch of the trigeminal nerve [ 12 ]. Previous studies found that decreased corneal sensitivity and decreased sub-basal nerve length were observed in all NK eyes [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is vital to thoroughly understand the mechanisms of the blink reflex when discussing trigeminal nerve damage combined with facial nerve damage. The corneal blink reflex is a loop between the facial nerve and the ophthalmic branch of the trigeminal nerve [ 12 ]. Previous studies found that decreased corneal sensitivity and decreased sub-basal nerve length were observed in all NK eyes [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The course of recovery after using this technique showed no side effects, while in the gold weight other side effects were found such as extrusion, infection, visibility, distortion of the upper eyelid, Plastic, Reconstructive Surgery and Burn occasional astigmatism and the cost of the gold plate). 3,5,8 The aesthetic appearance of the upper eyelid and patients' satisfaction after Paul Tessier's technique of (LPS) muscle lengthening was found far higher than in patients after using gold weight technique reported in the literature. 10 Guillou-Jamard et al 4 published a study of 29 patients who were treated with (LPS) muscle lengthening by aponeurosis interposition as Paul Tessier's description.…”
Section: Resultsmentioning
confidence: 83%
“…Multiple ocular disorders like conjunctivitis, keratitis, corneal ulceration, and vision loss result from the lack of ocular protection. [1][2][3][4][5][6][7][8][9][10][11] Facial palsy treatment necessitates a multidisciplinary approach. If a spontaneous recovery is predicted, temporary procedures like as artificial tears, lid taping overnight, viscous ointments, temporary tarsorrhaphy and external weights of the eyelid are recommended.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corneal neurotization can be performed either by directly transferring a nerve from its original position to supply the cornea (direct corneal neurotization, DCN) or by connecting a nerve to the cornea via nerve graft conduit (indirect corneal neurotization, ICN) [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Direct neurotization could perhaps achieve a faster clinical response, while indirect neurotization requires new axons to grow down the length of the nerve graft to the cornea and can take approximately 6 months.…”
Section: Corneal Neurotization—surgical Techniquesmentioning
confidence: 99%